Pengembangan Panduan Layanan Konseling Kelompok Berbasis Petualangan Untuk Meningkatkan Resiliensi Siswa SMP - Nurdestama, Handika Mulya; Flurentin, Elia; Ramli, M (citeus, 2025)
The research aims to develop an adventure-based group counseling service guide to improve student resilience. Adventure-based group counseling services are packaged in a guide that contains daily activities by reflecting on the actual situation and includes treatments to increase resilience. The researcher uses the Research and Development design developed by Borg and Gall with research steps: (1) data collection, (2) planning, (3) product development, (4) expert testing, (5) product design revision, (6) stage test potential users, (7) revise the product into a prototype. Researchers did not conduct field tests due to the Covid-19 pandemic. In the expert test, the product is tested by two experts in terms of material and media and then tested by potential users. The results of the expert and prospective user test assessments show that the guide in the form of a prototype has met the acceptance criteria, so it is feasible to use.